Intensifikasi Pendederan Ikan Jelawat (Leptobarbus hoevenii Blkr) dengan Peningkatan Padat Tebar Pada Sistem Resirkulasi - Harianto, Eko; Arifin, M Yusuf; Sugihartono, Muhammad; Pangentasari, Dwinda; Pertiwi, Anisa (Universitas Batangahari Jambi, 2025)
The nursing phase of Jelawat Fish (Leptobarbus hoevenii Blkr) is a crucial stage in aquaculture, where preparing healthy and robust fry poses a significant challenge. The availability of fry for grow-out activities remains low, consequently limiting the production of Jelawat Fish. This study aims to determine the optimal stocking density under an intensive culture system by evaluating production performance and physiological conditions in a recirculating system for 40 days. The study was conducted using a Completely Randomized Design with four treatments and three replications for each treatment: A (5 individuals/L), B (10 individuals/L), C (15 individuals/L), and D (20 individuals/L). The results showed that high stocking densities significantly affected absolute weight gain (AWG), absolute length gain (ALG), feed conversion ratio (FCR), weight variation coefficient (WVC), and length variation coefficient (LVC). The weight gain increased from 0.50±0.09 g/individual to between 1.51±0.03 g/individual and 1.86±0.05 g/individual, while the initial length of 4.10±0.29 cm/individual increased to a final range of 5.36±0.05 to 5.72±0.06 cm/individual. The lowest FCR was observed at a stocking density of 10 individuals/L (1.33), whereas the highest FCR was found at 20 individuals/L (1.52). Water quality parameters remained within the optimal range for Jelawat Fish culture throughout the study. Therefore, a stocking density of 10 individuals/L is recommended as the best option to achieve optimal growth while maintaining stable physiological conditions in fish.